2011
DOI: 10.1017/s1479262111000116
|View full text |Cite
|
Sign up to set email alerts
|

Iron biofortification of maize grain

Abstract: Mineral nutrient deficiencies are a worldwide problem that is directly correlated with poverty and food insecurity. The most common of these is iron deficiency; more than one-third of the world's population suffer from iron deficiency-induced anaemia, 80% of which are in developing countries. The consequences of iron deficiency include increased mortality and morbidity rates, diminished cognitive abilities in children and reduced labour productivity, which in turn stagnates national development. The developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…Maize ( Zea mays L.) is widely consumed in developing countries and provides energy, vitamins and minerals [8-15]. However, a major cause of Fe deficiency is poor intake of Fe, due to low bioavailability from plant-based diets containing mineral absorption inhibitors as polyphenols and phytates.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Maize ( Zea mays L.) is widely consumed in developing countries and provides energy, vitamins and minerals [8-15]. However, a major cause of Fe deficiency is poor intake of Fe, due to low bioavailability from plant-based diets containing mineral absorption inhibitors as polyphenols and phytates.…”
Section: Introductionmentioning
confidence: 99%
“…Research into the genetic basis for Fe nutritional quality in maize has established the potential for Fe biofortification, as Fe concentration and bioavailability are under genetic control and have demonstrated potential for improvement [8,9]. Previously, we utilized quantitative trait locus (QTL) mapping to characterize the genetic complexity of Fe concentration and bioavailability in maize [9,20,21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, research has demonstrated that the Caco-2 cell bioassay [20] is a fast and cost effective approach to screening of hundreds of samples and prior to the selection of the most promising lines to be assessed in vivo [21]. Subsequent feeding trials of the selected lines confirmed the enhanced Fe bioavailability developed via the in vitro screening [22]. …”
Section: Introductionmentioning
confidence: 99%